This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The final answer is -1 You wrote 1 but -3/3=-1
I have very limited mathmatical knowledge. How did you reduce the original question. I understand the why, but not how
Log in to reply
1 2 = 4 × 3 = 2 3 . Likewise 2 7 = 3 3 .
In you're second step what really happened? because I thought when simplyfied step 2 should equal to root 3 minus 3 root 3 times root 3 divided by 3???
Log in to reply
6 ( 2 3 − 3 3 ) 3 ⋅ 2 = 3 ( − 3 ) 3
That's exactly the same way I solved it !
I don't know why I can't submit my answer....just shows that give an integer..! What can I do?
Log in to reply
Just make sure you enter an integer without decimal. I have not experienced such problem.
This is wrong since √4 = ±2 So the answer is: -(±1) = ∓ 1
Log in to reply
No, x ≥ 0 for real value x ≥ 0 if not then 1 2 = ± 2 3 , 3 = ± 1 . 7 3 2 . . . = ± 3 . But 3 = − 3 .
Log in to reply
Why are you allowed to extend the numerator? Originally, it was only under the root 12 and root 27, but then you extended it under the root 3 and root 4? Are you allowed to do that? My brain must be fuzzy.
Log in to reply
@Tyler Cade Richardson – 1 2 = 4 × 3 = 2 3 . Likewise 2 7 = 3 3 .
x 2 = ± x , So 3 × 3 = ± 3 , which leads to ± 1 as the answer.
Log in to reply
@Ciprian Coca – No, x ≥ 0 for real value x ≥ 0 if not then 1 2 = ± 2 3 , 3 = ± 1 . 7 3 2 . . . = ± 3 . But 3 = − 3 .
Log in to reply
@Chew-Seong Cheong – But why do we assume that sqrt of a given number is its principal(positive) one? Are we given any parameters or limits that imply this?
Log in to reply
@Tyvon O - Addo – x = f ( x ) is a function of x , a f ( x ) has only one unique value. Therefore, x has only one value. When we have x 2 = 3 , we said that x = ± 3 , that is because, we don't know before hand if x is positive or negative and therefore, both 3 and − 3 can be x . But when we use x it means that it is ≥ 0 .
6 1 2 − 2 7 × 3 × 4
= 6 3 ( 4 − 9 ) × 3 × 4
= 6 4 − 9 × 3 × 2
= 6 4 − 9 × 6
= 4 − 9 = 2 − 3 = − 1
Brilliant approach! Good work!
This was the best explanation
Great approach!
{[(Sqrt 12)-(Sqrt 27)]/6} (Sqrt 3) (Sqrt 12)=[12-(Sqrt 324)]/6=(12-18)/6=-6/6=-1. Answer -1.
6 1 2 − 2 7 × 3 × 4
First we turn them all into radical form,
( 3 6 1 2 − 3 6 2 7 ) × 1 2
= 3 6 1 4 4 − 3 6 3 2 4
= 4 − 9
= 2 − 3
= − 1
Under what assumption you took sqrt(4)=2? sqrt(4) = 2 or -2. Same applicable for sqrt(9)!
Log in to reply
No, the radical sign (√) denotes only the principal square root, which is always positive. So while 4 has two square roots, +2 and -2, √4 = 2. Indeed, a = ±√(a^2), because √(a^2) = |a|
6
1
2
−
2
7
×
3
×
4
=
3
6
2
3
−
3
3
×
3
×
4
=
2
×
3
×
3
−
3
×
3
×
2
=
−
1
6 3 ⋅ 4 − 3 ⋅ 9 × 3 × 4
= 6 3 ( 3 ⋅ 2 − 3 ⋅ 3 ) × 2
= 6 ( ( 3 ⋅ 2 ) − ( 3 ⋅ 3 ) ) × 2
= 3 6 − 9 = − 1
sqrt{4} = 2 or -2. Under what assumption you took sqrt{4} = 2 only?
hello see this java code:
public class IAmBrilliant {
public static void main(String[] args){
System.out.println((Math.sqrt(12)-Math.sqrt(27))/6*Math.sqrt(3)*Math.sqrt(4));
}
}
it outputs:
-1.0
anyone know how to do it using math?
6 1 2 − 2 7 × 3 × 4 = 6 2 3 − 3 3 × 2 3 = 6 ( 2 − 3 ) 3 × 2 3 = 6 − 3 × 2 3 = 6 − 2 ( 3 ) ∵ 3 × 3 = 3 = 6 − 6 = − 1
1
.
6
1
2
−
2
7
×
3
×
4
−
G
i
v
e
n
2
.
=
6
4
×
3
−
9
×
3
×
3
×
2
−
B
r
e
a
k
R
a
d
i
c
a
l
s
I
n
t
o
S
q
u
a
r
e
s
3
.
=
6
4
×
3
−
9
×
3
×
2
3
−
S
i
m
p
l
i
f
y
R
a
d
i
c
a
l
s
4
.
=
6
2
3
−
3
3
×
2
3
−
S
i
m
p
l
y
R
a
d
i
c
a
l
s
5
.
=
6
−
1
3
×
1
2
3
−
C
o
m
b
i
n
e
L
i
k
e
T
e
r
m
s
6
.
=
6
−
1
3
×
2
3
−
M
u
l
t
i
p
l
y
F
r
a
c
t
i
o
n
s
7
.
=
6
−
1
×
2
×
3
×
3
−
C
o
m
m
u
t
a
t
i
v
e
P
r
o
p
e
r
t
y
8
.
=
6
−
2
×
3
=
6
−
6
=
−
1
−
S
i
m
p
l
i
f
y
6 1 2 − 2 7 × 3 × 4
= 2 × 3 3 × 4 − 3 × 9 × 3 × 2
= 3 2 3 − 3 3 × 3
= − 3 3 × 3
= − 3 3 = − 1
It's simple guys. Just convert all roots to whole numbers(i.e √4 = 2) and then convert 6 to corresponding roots. Then you'll just need to use some sense to simplify the answer.( I am a 10th grader and did this sum in 20 secs)
1 2 = 2 3
2 7 = 3 3
2 3 − 3 3 = − 1 3
3 × 4 = 1 2 = 2 3
6 2 3 = 3 3
3 3 × − 1 3 = 3 − 3 = − 1
Hi Bob, to write a formula in Latex, enclose your formula inside \ ( \ ) .
I have edited your solution to make your math look beautiful. You can press the "edit" button to see its code.
There is no need of solution its a basic concept which only need a little focus
((√12 - √27) / 6 ) x √3 x √4 = ( (2√3-3√3) x √3x2 ) / 6 = ( 4√9 - 6√9 ) / 6 = (4x3 - 6x3)/ 6 = ( 12 - 18 ) / 6 = -6 /6 = -1
Its amazing how many different ways there are to solve this problem. And this is the reason why math is such a beautiful subject.
6 1 2 − 2 7 × 3 × 4 = 1 2 × 6 1 2 ( 2 3 − 3 3 ) = 6 1 2 × − 3 = 6 − 3 6 = 6 − 6 = − 1
Problem Loading...
Note Loading...
Set Loading...
6 1 2 − 2 7 × 3 × 4 = 6 ( 2 3 − 3 3 ) 3 ⋅ 2 = 3 ( − 3 ) 3 = 3 − 3 = − 1